EMERGENCY CONSTITUTIONAL LAW BASED ON LAW NUMBER 23 PRP OF 1959 ON THE STATE OF DANGER - Hotmaida Simanjuntak; A. Ismail S; Syahdi Firman (JOURNAL EQUITABLE, 2024)
Emergency Constitutional Law is Constitutional Law that applies in a state of emergency or Constitutional Law that applies when the State is in a state of emergency. Emergency Constitutional Law is part of ordinary Constitutional Law but contains special norms. Specific norms in the Emergency Constitutional Law are limited in their application only in abnormal circumstance normative juridical method. The nature of this research is descriptive, namely research intended to provide a clearer picture and apply the existing reality in clear and systematic detail regarding the main research problem. Implementation of Emergency Constitutional Law Based on Law Number 23 Prp of 1959 concerning Dangerous Conditions, namely that regional governments have not yet been maximally involved, the existence and position of regional governments is very important and is an important pillar that supports the continuity of the implementation of the power of the government of the Unitary State of the Republic of Indonesia, apparently in The emergency authority it has not yet parallel to its very important existence and position. Regional governments do not yet have maximum and meaningful authority to activ, take decisions or take the initiative to make important and basic policies to overcome emergencies at the regional level.